Anti-Melanogenic Effects of Takifugu flavidus Muscle Hydrolysate in B16F10 Melanoma Cells and Zebrafish - Hu, Jinjin; Chen, Bei; Qu, Shuaijie; Liu, Shuji; Yang, Xiaoyu; Qiao, Kun; Su, Yongchang; Liu, Zhihui; Chen, Xiaoe; Liu, Zhiyu; Wang, Qin (Marine drugs, 2024)
Abnormal melanogenesis can lead to hyperpigmentation. Tyrosinase (TYR), a key rate-limiting enzyme in melanin production, is an important therapeutic target for these disorders. We investigated the TYR inhibitory activity of hydrolysates extracted from the muscle tissue of Takifugu flavidus (TFMH). We used computer-aided virtual screening to identify a novel peptide that potently inhibited melanin synthesis, simulated its binding mode to TYR, and evaluated functional efficacy in vitro and in vivo. TFMH inhibited the diphenolase activities of mTYR, reducing TYR substrate binding activity and effectively inhibiting melanin synthesis. TFMH indirectly reduced cAMP response element-binding protein phosphorylation in vitro by downregulating melanocortin 1 receptor expression, thereby inhibiting expression of the microphthalmia-associated transcription factor, further decreasing TYR, tyrosinase related protein 1, and dopachrome tautomerase expression and ultimately impeding melanin synthesis. In zebrafish, TFMH significantly reduced black spot formation. TFMH (200 μg/mL) decreased zebrafish TYR activity by 43% and melanin content by 52%. Molecular dynamics simulations over 100 ns revealed that the FGFRSP (T-6) peptide stably binds mushroom TYR via hydrogen bonds and ionic interactions. T-6 (400 μmol/L) reduced melanin content in B16F10 melanoma cells by 71% and TYR activity by 79%. In zebrafish, T-6 (200 μmol/L) inhibited melanin production by 64%. TFMH and T-6 exhibit good potential for the development of natural skin-whitening cosmetic products.